Implementasi Teknologi Penjernih Air Payau Berbasis Alat Penjernih Air Payau Berbasis Bahan Lokal (ALPAMAL) dalam Mengatasi Krisis Air Bersih - Hermawan, Surya; Hosea, Felixiano; Theodore, Stanley; Njo, Anastasia; Harjanti, Dhyah (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The coastal community of Tegalsari Hamlet, Dukuh Kupang Village, Sidoarjo, is facing a clean water crisis due to dependence on brackish water sources with Total Dissolved Solid (TDS) reaching 6000 mg/L, which is considered very dangerous. To overcome this problem, the community service team developed a brackish water purifier based on local materials (ALPAMAL) using environmentally friendly technology. This activity uses the Participatory Action Research (PAR) method combined with service learning, involving the community in every stage, from identifying problems, designing the tool, to implementation and evaluation. The survey results showed that 96% of the community wanted ALPAMAL for clean water needs, and 93% were willing to maintain the tool. This program proves that simple, participation-based technology can be a sustainable solution in dealing with the air crisis in coastal areas, as well as increasing community independence in managing air resources.